An electrophoretic approach to reveal the freshness of buffalo mozzarella cheese. (October 2022) - Rutigliano, Mariacinzia; Spadaccino, Giuseppina; Gagliardi, Rosa; Di Luccia, Aldo; Faccia, Michele; la Gatta, Barbara
Abstract: Freshness is one of the more appreciated attributes for high moisture buffalo mozzarella cheese (BMC) that guarantees highest quality for the consumer. However, freshness decreases during shelflife of this cheese due to proteolysis events caused mainly by milk endogenous enzymes, such as plasmin. Plasmin generated γ-casein (γ-CN) fragments from β-CN proteolysis can be assessed by SDS-PAGE and image analysis; β-CN decrease and γ-CN increase represent useful markers to obtain an index of freshness (Φ). For this purpose, a "Control Line" was assessed analysing BMC with PDO certification. Samples were stored under different conditions (room temperature, refrigerated and frozen) for different times. Moreover, 145 BMC samples purchased from markets were studied to understand if the calculated Φ was consistent with the Control Line study results. Assessing the proteolysis mechanism for formation of γ-CN fragments provides a reliable method to evaluate freshness of PDO BMC during storage of this typical Italian product.